Mood, mileage and the menstrual cycle. Issue 3 (September 1992) - Cockerill, I M; Nevill, A M; Byrne, N C
Abstract : Forty women took part in a study to determine the effects of high-intensity training and the menstrual cycle on mood states. Half of the sample were competitive distance runners following a training load of between 50 km and 130 km running per week. Seven athletes were amenorrhoeic and 13 either eumenorrhoeic or oligomenorrhoeic. The remaining 20 subjects were inactive women who menstruated regularly. The mean age of all 40 subjects was 29 years. Each subject completed two identical Profile of Mood States (POMS) questionnaires. The 33 menstruating subjects completed both a premenstrual and a midcycle form and the amenorrhoeic athletes completed the questionnaires at a 3-week interval, which acted as a control for the potential effects of premenstrual syndrome (PMS) among the menstruating females. Results showed highly significant differences in mood profiles among amenorrhoeic athletes, non-amenorrhoeic athletes and inactive women. The greatest difference was between premenstrual and midcycle measures for the inactive group. PMS appears to cause marked negative mood swings among menstruating women which the POMS inventory is sensitive in detecting. While the lower-intensity-training runners appeared to benefit psychologically from a training distance of approximately 50 km week-1, high-intensity training had an adverse effect on mood.